A case study strategy as part of an information systems research methodology: a critique. (1st January 1999) - Irani, Z.; Ezingeard, J.-N.; Grieve, R.J.; Race, P.
A case study strategy as part of an Information Systems (IS) research methodology embodies a unique style and is one that can employ a variety of research methods. This scientific approach to research appears to be increasing in popularity in the area of IS, and is providing a legitimate alternative to the more traditional lines of enquiry. The authors of this paper identify the underlying purpose of a case study strategy and describe its research objectives. These typically include a strategy for (i) discovery and theory building; (ii) theory testing; and (iii) discovery, theory building and theory testing. The authors then debate the merits of a single versus multiple-case study design. This is followed by a discussion of the positivist and interpretivist epistemological approaches that a case study research strategy can take, drawing case study examples from the published IS literature, thus facilitating in the establishment of the readers epistemological stance. The authors then review the characteristics inherent in quantitative and qualitative research methods, which are summarised in a taxonomy. Finally, the authors conclude by stressing the suitability of a case study strategy when part of an IS research methodology.